Genetic profile of primary mucinous cystadenocarcinoma of the breast—A case report. Issue 9 (28th June 2021) - Lin, Lawrence Hsu; Hernandez, Osvaldo; Zhu, Kelsey; Guth, Amber; Cotzia, Paolo; Darvishian, Farbod
Abstract: Primary mucinous cystadenocarcinoma of the breast is a rare neoplasm with few reports in the literature. Here, we report for the first time a comprehensive genetic profile of a primary mucinous cystadenocarcinoma of the breast, using next‐generation sequencing 580 cancer‐associated gene panel. Mutations in TP53, RB1, and BAP1 were identified. The findings suggest that this tumor is driven mostly by abnormalities in tumor suppressor genes, primarily involved in cell cycle control and chromatin remodeling. Molecular characterization of additional primary mucinous cystadenocarcinomas of the breast is warranted and might provide information related to its biology and behavior.